Metode Estimasi Suhu Minyak pada Transformator Tenaga melalui Pengukuran Suhu Body Berbasis IoT - Rizal Alfa Rizki; Dista Yoel Tadeus; Fakhruddin Mangkusasmito; Heru Winarno; Eko Ariyanto (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
Oil cooled power transformer has important role in the electricity distribution system. Its windings were immersed in oil as an insulating medium and also as a cooler. This oil would be heated up due to several things, the most significant was heat generated by winding’s power loss. The monitoring of oil temperature on the transformer was always done routinely every day to maintain its performance and health condition. IoT based measurements could improved efficiency and minimized manpower resources. To realize this the indirect non-destructive measurement method was proposed to estimate transformator’s temperature oil. It will corellate the oil temperature and body temperature through a constant calibration factor derived from calculations. Conducted experiment applied to specific existing transformator and followed by calculations resulted a calibration factor = 1.7749. The smallest average of estimated temperature error was lied in the range of 40 - 90 degrees Celcius.